Gynaecological and other health problems of postmenopausal women and their health seeking behaviour in rural Terai, Nepal (Health Renaissance, 2015)
Background: There is very few data available in menopausal study done in Nepal.   The data is even less on the various gynecological and medical problems postmenopausal women are suffering from. This study was done in Duhabi area, a community in Eastern Nepal, around the Comprehensive Health Service area of a   community hospital under B.P Koirala Institute of Health Sciences.Objective: This study was done to document the various gynecological problems among the postmenopausal   women and their relation with the socio-demographic characteristics.Methods: By using specific questionnaire, 234 post-menopausal women were   interviewed regarding menopausal symptoms, other gynaecological problems and   medical problems and their health seeking behaviour. Results: Our study showed   that the most common symptoms among the post-menopausal women were loss of libido (53%) and hot flushes (41.5%). Other noted symptoms found were vaginal   dryness (29.1%) and excessive vaginal bleeding (14.5%). The most common urinary symptoms were urgency (34.2%), dysuria (17.1%) and incontinence (17.1%). Uterine prolapse was reported by 6.4% of respondents. The most common medical condition seen in our study was low back ache (70.1%). Despite majority (62%) seeking medical treatment for their symptoms only 1.7% of the respondents were using hormone replacement therapy.Conclusion: The prevalence of gynaecological problems among the post-menopausal women was high in our study with the main symptoms of loss of libido and hot flushes. Majority of women with postmenopausal   symptoms sought medical care for their problems.   Health Renaissance 2014;12(2): pp: 87-91